2006
DOI: 10.1590/s0100-69162006000200013
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento e identificação dos símbolos gráficos utilizados para a caracterização de controles e comandos em máquinas agrícolas

Abstract: RESUMO:Os símbolos gráficos utilizados para indicar a função dos comandos e controles das máquinas agrícolas tornam a operação mais segura. Logo, este trabalho teve por objetivo identificar a simbologia existente nas máquinas agrícolas disponíveis nas quatro principais concessionárias de Santa Maria -RS. No levantamento, foram utilizados como parâmetros os símbolos gráficos recomendados pelas normas técnicas, sendo os existentes nas máquinas estudadas fotografados e posteriormente anotados em planilha. O resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…So the three evaluated agricultural harvesters had a C rating for they did not show function indicators which can be easily understood by operator as well as the position and the distance of control commands. Alonço et al (2006) stated that graphic symbols used to indicate machitrol functions accomplish a safer operation. Symbols were standardized according to Alonço et al (2007) after Regulatory Norm NBR 11379, aiming at standardizing graphic symbols for operational command identification and machinery maintenance.…”
Section: Resultsmentioning
confidence: 99%
“…So the three evaluated agricultural harvesters had a C rating for they did not show function indicators which can be easily understood by operator as well as the position and the distance of control commands. Alonço et al (2006) stated that graphic symbols used to indicate machitrol functions accomplish a safer operation. Symbols were standardized according to Alonço et al (2007) after Regulatory Norm NBR 11379, aiming at standardizing graphic symbols for operational command identification and machinery maintenance.…”
Section: Resultsmentioning
confidence: 99%
“…This fact demonstrated that there is no supply uniformity by the manufacturing companies in lighting and signaling elements for traffic on agricultural tractors models. The agricultural machines manufacturers, despite knowing certain technical standards, do not use them in a correct and homogeneous way, what contribute to the tractors models offered in Brazil are not standardized (ALONÇO et al, 2006). BAESSO et al (2018) with the objective of observing the existence of ergonomics and safety items in agricultural tractors and comparing the results with the respective Brazilian laws, observed that 48% of the tractors studied did not meet these standards.…”
Section: Rural Engineeringmentioning
confidence: 99%
“…According to Alonço, Balestra, Dias, and Medeiros (2006), the graphic symbols used in agricultural machinery make the operation safer. However, according to Alonço, Machado, Ferreira, and Medeiros (2007), even though these pictographs are present in these machines, their understanding by the major agents in the process is greatly reduced.…”
Section: Acta Scientiarum Technologymentioning
confidence: 99%